2004
DOI: 10.1002/pen.20096
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of polyolefin‐clay nanocomposites

Abstract: Polyolefin-organoclay nanocomposites containing a synthetic tetrasilisic fluoromica were prepared from metallocene-catalyzed and conventional Ziegler-Natta-catalyzed linear low-density polyethylenes (LLDPE) by means of melt-compounding. The effects of maleic-anhydride grafted compatibilizer (PE-g-MA) level, clay concentration, and blending procedure were investigated and compared. Morphology and structural analysis using transmission electron microscopy (TEM) and X-ray diffraction (XRD) suggested the clay exfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 39 publications
(18 reference statements)
1
27
0
Order By: Relevance
“…Recent much research has shown that 14/28 siloxane-based organic-inorganic hybrid materials prepared by the hydrolysis-condensation of alkoxysilane compounds can be controlled at the nanometer length scale through self-assembly. For instance, the formation of a layer structure composed of alkyl chains with all-trans conformations has been reported for the products obtained by the hydrolytic condensation of alkyltrialkoxysilanes or alkyltrichlorosilanes (12)(13)(14)(15)(16)(17)(18) carbon atoms in the alkyl group) [60][61][62][63][64][65]. Those results are an aid in understanding the formation of the highly-ordered structure in water-crosslinked EPR-g-VTMS/HTMS composites.…”
Section: Absolute Configuration Of Water-crosslinked Epr-g-vtms/htms mentioning
confidence: 86%
“…Recent much research has shown that 14/28 siloxane-based organic-inorganic hybrid materials prepared by the hydrolysis-condensation of alkoxysilane compounds can be controlled at the nanometer length scale through self-assembly. For instance, the formation of a layer structure composed of alkyl chains with all-trans conformations has been reported for the products obtained by the hydrolytic condensation of alkyltrialkoxysilanes or alkyltrichlorosilanes (12)(13)(14)(15)(16)(17)(18) carbon atoms in the alkyl group) [60][61][62][63][64][65]. Those results are an aid in understanding the formation of the highly-ordered structure in water-crosslinked EPR-g-VTMS/HTMS composites.…”
Section: Absolute Configuration Of Water-crosslinked Epr-g-vtms/htms mentioning
confidence: 86%
“…In other words the smaller 2nd peak for mic-CHD-N6 compared for example to mic-CHD-N2 reveals this fact that there is more melted material at microcellular processing temperature for the first mentioned sample. The reason for this increase returns to the fact that by increasing the nano-clay content the nucleation sites increase which lead to smaller but more populated spherulites [23][24][25][26] in the bulk-phase matrix during the composite production process. This means more edge areas for spherulites.…”
Section: Thermal Behavior; Melting Studymentioning
confidence: 93%
“…Besides surface modification of clay, compatibilizing agents, which are materials composed of a hydrophilic part to be compatible with clay while the other part is hydrophobic to blend with the polymer matrix, might be considered to help prepare polyolefin/clay nanocomposites since they increase the interfacial interaction between organophilic clay and a hydrophobic polymer matrix. [16][17][18][19][20] It is reasonable to suggest that a detailed look at the role of miscibility and solubility of the compatibilizer with the matrix as a significant parameter in affecting the dispersion of clay in the high-density polyethylene (HDPE), could help to better understand the importance of polymer/compatibilizer interaction at a molecular level. Different aspects of compatibilizers, such as the effects of type, amount, and MA-group content of compatibilizers, on the extent of intercalation/exfoliation have been studied by various researchers.…”
Section: Introductionmentioning
confidence: 99%